2023
DOI: 10.1007/s00394-023-03096-x
|View full text |Cite
|
Sign up to set email alerts
|

Anti-obesity effects of Lactiplantibacillus plantarum SKO-001 in high-fat diet-induced obese mice

Abstract: Purpose Previous reports showed that some probiotics provide beneficial effects on various diseases including metabolic disorders. This study aimed to investigate the anti-obesity effects of Lactiplantibacillus (L.) plantarum SKO-001 (SKO-001), a probiotic strain newly isolated from Angelica gigas. Methods C57BL/6J mice were fed with high-fat diet (HFD, 60% fat) for four weeks, and then different doses of SKO-001 (n = 10 each group) were orally given for 1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
10
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 39 publications
0
10
0
Order By: Relevance
“…These results are consistent with research showing an increase in serum adiponectin levels, a decrease in LDL-C levels, and a decrease in body fat mass in rats. Some L. plantarum strains have been shown to decrease the mRNA levels of adipogenic genes, including SREBP-1c, PPAR-γ, and C/EBPα [ 13 ]. Similarly, SKO-001 reduced lipid accumulation in the liver, lowered mRNA levels of lipogenic genes, and reduced α-smooth muscle actin and collagen type 1 alpha 1 levels [ 13 ].…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…These results are consistent with research showing an increase in serum adiponectin levels, a decrease in LDL-C levels, and a decrease in body fat mass in rats. Some L. plantarum strains have been shown to decrease the mRNA levels of adipogenic genes, including SREBP-1c, PPAR-γ, and C/EBPα [ 13 ]. Similarly, SKO-001 reduced lipid accumulation in the liver, lowered mRNA levels of lipogenic genes, and reduced α-smooth muscle actin and collagen type 1 alpha 1 levels [ 13 ].…”
Section: Discussionmentioning
confidence: 99%
“…One of the emerging potentially effective treatments for obesity prevention and/or treatment is the intake of probiotics to alter the composition of the gut microbiome [ 11 ]. Previous studies have reported that the probiotic Lactiplantibacillus plantarum , SKO-001, K50, KY1032, and LMT1-48 can reduce obesity and improve weight- or body fat-related indicators, possibly via the regulation of lipid metabolism [ 12 , 13 , 14 , 15 , 16 ].…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations